2012
DOI: 10.1128/aac.05526-11
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Antituberculosis Drug Concentrations in HIV-Infected Patients Who Are Men or Have Low Weight: Implications for International Dosing Guidelines

Abstract: .1% (95% CI, 2.7, 9.6) and 6.0% (95% CI, 0.8, 11.3) for rifampin, isoniazid, pyrazinamide, and ethambutol, respectively. Males had day 29 AUC 0-12 s 19.3% (95% CI, 3.6, 35.1) and 14.0% (95% CI, 5.6, 22.4) lower than females for rifampin and pyrazinamide, respectively. Level of immune suppression and concomitant antiretrovirals had little effect on the concentrations of the antituberculosis agents. As they had reduced drug concentrations, it is important to review treatment responses in patients in the lower we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
87
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 37 publications
13
87
2
2
Order By: Relevance
“…Their baseline characteristics are presented in Table 1, and further information can be found in the previous report (12). The median weight, FFM, and height were 55.2 kg, 42.2 kg, and 1.59 m, respectively.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their baseline characteristics are presented in Table 1, and further information can be found in the previous report (12). The median weight, FFM, and height were 55.2 kg, 42.2 kg, and 1.59 m, respectively.…”
Section: Demographicsmentioning
confidence: 99%
“…Additionally, a sample was collected at approximately 12 h before the 15th dose. Details of plasma separation and storage and quantitation of drug concentrations were as reported before (12). The lower limit of quantitation was 0.1 mg/liter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low rifampin exposure among undernourished TB HIV-coinfected patients has been reported previously; a study by Polasa et al assessing rifampin kinetics in undernourished individuals shows that AUC and C max were reduced in undernourished individuals compared to individuals with normal BMI (9). McIlleron et al also reported reduced rifampin exposure among undernourished HIV-coinfected TB patients in studies from South Africa (8,35). A recent study from South Africa by Pasipanodya et al has also shown that serum drug concentrations predicted clinical outcome in TB patients and that low rifampin and isoniazid C max and AUC preceded therapy failure and occurrence of multidrug resistance or extremely drug-resistant TB (36).…”
Section: Discussionmentioning
confidence: 82%
“…Our sample size was small and many factors may have influenced the pharmacokinetics, including extremes of weight and days on treatment. [29] The lack of a control group may also be viewed as a limitation of our study. We used historical pharmacokinetic data in our analysis, as it was deemed impractical and unethical to subject 10 healthy volunteers to 7 days of TB treatment, a nasogastric feeding tube and 24 hours of pharmacokinetic sampling.…”
Section: Fig 2 Isoniazid Plasma Concentration Over Time (0 -24 Hourmentioning
confidence: 99%